Is there a need for formal undergraduate patient handover training and could an educational workshop effectively provide this? A proof-of-concept study in a Scottish Medical School. Issue 2 (12th February 2020) - Holt, Nicholas; Crowe, Kirsty; Lynagh, Daniel; Hutcheson, Zoe
Abstract : Background: Poor communication between healthcare professionals is recognised as accounting for a significant proportion of adverse patient outcomes. In the UK, the General Medical Council emphasises effective handover (handoff) as an essential outcome for medical graduates. Despite this, a significant proportion of medical schools do not teach the skill. Objectives: This study had two aims: (1) demonstrate a need for formal handover training through assessing the pre-existing knowledge, skills and attitudes of medical students and (2) study the effectiveness of a pilot educational handover workshop on improving confidence and competence in structured handover skills. Design: Students underwent an Objective Structured Clinical Examination style handover competency assessment before and after attending a handover workshop underpinned by educational theory. Participants also completed questionnaires before and after the workshop. The tool used to measure competency was developed through a modified Delphi process. Setting: Medical education departments within National Health Service (NHS) Lanarkshire hospitals. Participants: Forty-two undergraduate medical students rotating through their medical and surgical placements within NHS Lanarkshire enrolled in the study. Forty-one students completed all aspects. Main outcome measures: Paired questionnaires, preworkshop and postworkshop, ascertained prior teaching and confidence in handover skills. The questionnaires also elicited the student's views on the importance of handover and the potential effects on patient safety. The assessment tool measured competency over 12 domains. Results: Eighty-three per cent of participants reported no previous handover teaching. There was a significant improvement, p<0.0001, in confidence in delivering handovers after attending the workshop. Student performance in the handover competency assessment showed a significant improvement (p<0.05) in 10 out of the 12 measured handover competency domains. Conclusions: A simple, robust and reproducible intervention, underpinned by medical education theory, can significantly improve competence and confidence in medical handover. Further research is required to assess long-term outcomes as student's transition from undergraduate to postgraduate training.